а можно задание на русском?
упростите выражение

Ответы и объяснения

2014-03-10T23:09:52+04:00
 (\frac{2ab}{(a-b)(a+b)} + \frac{a-b}{2(a+b)} )*  \frac{2a}{b+a} + \frac{b}{b-a} = \\  =\frac{4ab+(a-b)^{2} }{2(a-b)(a+b)}* \frac{2ab-2a^{2} +b^{2} +ab}{(b-a)(b+a)}  = \\ = \frac{(4ab+a^{2} -2ab+b ^{2}) *(-2a^{2}+ab+b ^{2}) }{2(a-b)(a+b)^{2}(b-a)}=  \\ =\frac{(a+b) ^{2}  *(-2a^{2}+ab+b ^{2}) }{2(a-b)(a+b)^{2}(b-a)} = \\ =\frac{-2a^{2}+ab+b ^{2} }{2(a-b)(b-a)}
дальше не знаю как. может больше никак не сократить